The Expanding role of the human resources manager - Desatnick, Robert L. (New York : AMACOM, 1979)
Monograph on the role of the human resources manager in USA private enterprises, seen as a profit-oriented member of top management with greater involvement in organization development and employment policy than the traditional personnel management officer - includes human resources planning, labor costs, training, promotion, labor relations, wage determination, management development, management by objectives and legal aspects, and considers recruitment of the human resources manager. Diagrams
1. Mounting Concerns of the CEO -- 2. Influencing the Management Process -- 3. Achieving Impact at the Policy Level -- 4. Implementing and Obtaining Results -- 5.Focusing on New Standards and Measurements -- 6. Profiling the Function and Identifying the Incumbent -- 7. The Future: Phase IV.
Includes index.
Keywords: HUAMN RESOURCES